2020
DOI: 10.3390/su12093626
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Health Concerns for the Users of a Playground, Built with Reused Rotor Blades from a Dismantled Wind Turbine

Abstract: This paper analyses the user safety of a playground built out of reused blades from a dismantled wind turbine. Located in Rotterdam and designed by the Netherlands architecture firm Superuse Studios, the playground, called “Wikado”, represents an example of the circular economy applied to the built environment. With reused materials, Wikado represents a saving in resources and energy, when compared to a standard playground built with primary materials. Furthermore, the playground creates a unique design experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…All of these pose a threat to human health and the environment. Zappeloni [73] discusses best practices to minimise such emissions in the manufacturing stage, and Medici expressed concerns over long-term outdoor exposure [74]. Additionally, (re)processing, which aims to separate, or at least downsize the materials, risks hazardous emissions [7,72,75].…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…All of these pose a threat to human health and the environment. Zappeloni [73] discusses best practices to minimise such emissions in the manufacturing stage, and Medici expressed concerns over long-term outdoor exposure [74]. Additionally, (re)processing, which aims to separate, or at least downsize the materials, risks hazardous emissions [7,72,75].…”
Section: Limitations and Recommendationsmentioning
confidence: 99%
“…Wikado speaks for sustainable, circular solutions in terms of the reuse of materials and components. As Medici et al (2020) [63] reported, the content of the CE is crucial to reconsider strategies regarding the reuse of resources and materials.…”
Section: The Netherlandsmentioning
confidence: 99%
“…Joining up the start and the end of low-carbon infrastructure supply chains, resource security concerns [102,106,107], design for recycling [108,109] and supply chain security and development [95,103] are covered. Solutions that go beyond material recovery are emerging with publications on lifetime extension [110,111], eco-design [7], reuse and repurposing [83,93,112,113] and remanufacturing [114]-terminology explained in Section 4.…”
Section: Current Circular Economy Literature On Wind Energymentioning
confidence: 99%